Composition-driven inverse-to-conventional transformation of electrocaloric effect and large energy storage density in strontium modified Ba(Zr0.1Ti0.9)O3 thin films. Issue 4 (20th December 2019) - Sun, Yunlong; Zhang, Le; Wang, Haoyu; Guo, Mengyao; Lou, Xiaojie; Wang, Danyang
Abstract : Composition-tunable electrocaloric effect and large energy storage density with excellent thermal stability arising from synergistic effects of polar nano-regions and conformed defect dipoles were discovered in (Ba1− x Sr x )Zr0.1 Ti0.9 O3 thin films. Abstract : In this work, (Ba1− x Sr x )Zr0.1 Ti0.9 O3 (BSZT x, x = 0, 0.15, 0.25 and 0.35) thin films were successfully deposited on La0.7 Sr0.3 MnO3 (LSMO)-coated (001) SrTiO3 (STO) single crystal substrates using laser molecular beam epitaxy. The BSZT x thin films with compositions of x = 0 and 0.15 display an inverse electrocaloric effect (ECE) with a maximum adiabatic temperature change of Δ T ∼ −10 K under 1500 kV cm −1, while a large positive Δ T amounting to ∼13 K is discovered in the strontium rich composition, i.e. x = 0.35. For the composition of x = 0.25 where weak ECE (|Δ T | < 2 K) is discovered, an energy storage density of 15.5 J cm −3 with an efficiency of 69.8% is observed in the temperature range of 303–413 K. The composition-tunable electrocaloric effect and large energy storage density with excellent thermal stability in strontium modified Ba(Zr0.1 Ti0.9 )O3 thin films are ascribed to the synergistic effects of different dynamics of polar nano-regions (PNRs) and conformed defect dipoles under large electric fields at elevated temperatures. This work will facilitate the development of novel solid-state cooling devices and provide a design route for high energy storage density devices.